Factors influencing career intentions on completion of general practice vocational training in England: a cross-sectional study. Issue 8 (17th August 2017) - Dale, Jeremy; Russell, Rachel; Scott, Emma; Owen, Katherine
Abstract : Objectives: General practice is experiencing a growing crisis with the numbers of doctors who are training and then entering the profession in the UK failing to keep pace with workforce needs. This study investigated the immediate to medium term career intentions of those who are about to become general practitioners (GPs) and the factors that are influencing career plans. Design: Online questionnaire survey, with quantitative answers analysed using descriptive statistics and free text data analysed using a thematic framework approach. Setting and participants: Doctors approaching the end of 3-year GP vocational training in the West Midlands, England. Results: 178 (57.2%) doctors completed the survey. Most participants planned to work as salaried GPs or locums rather than entering a general practice partnership for at least the first 5 years post-completion of training; others failed to express a career plan or planned to leave general practice completely or work overseas. Many were interested in developing portfolio careers. The quality of general practice experience across undergraduate, foundation and vocational training were reported as influencing personal career plans, and in particular perceptions about workload pressure and morale within the training practices in which they had been placed. Experience of a poor work–life balance as a trainee had a negative effect on career intentions, as did negative perceptions about how general practice is portrayed by politicians and the media. Conclusion: This study describes a number of potentially modifiable factors related to training programmes that are detrimentally influencing the career plans of newly trained GPs. In addition, there are sociodemographic factors, such as age, gender and having children, which are also influencing career plans and so need to be accommodated. With ever-increasing workload in general practice, there is an urgent need to understand and where possible address these issues at national and local level.